Synergic Model Between Strategic Planning, Shared Value and Curricular Flexibility - Urcid-Puga, Rodrigo (2020)
This text aims to present, graphically, the interaction between strategic planning, shared value, curricular flexibility, higher education institutions (HEI), and the sociocultural environment surrounding all these topics. For the elaboration of this text, we implemented a cross-sectional qualitative methodology, supported by documented research, whose variables were not modified. As conclusions and findings, it was possible to verify the existence of a relation between subjects linked to strategic planning and curricular flexibility; it was also possible to relate issues, such as shared value and sociocultural environment, to create a specific context. Finally, the implications of this project lie in the fact that HEI should consider strategic planning as a fundamental tool to seek changes within these institutions and understand the relationship they have with their immediate environment when generating shared value.